Community Empowerment in Early Detection of Cervical Cancer in Female Age Women in Correctional Institution Women on Medan City - Lubis, Halinda Sari; Syarifah (Talenta Publisher, 2021)
Cancer in Indonesia is the number seven cause of death with a percentage of 5.7 percent of all causes of death. In North Sumatra, the prevalence of cancer in the population of all ages has increased, in 2013 it was 1 percent. How to detect cancer can be done with the Intra Visual Infection Test of Acetic Acid (IVA). The IVA test can be done at the Puskesmas, but in Medan City WUS who carry out the IVA test only reaches 30% of the target set. In the Women's District of Medan City, the IVA test problem at WBP is still low. They do not know the benefits of the test even though they know that cervical cancer is a deadly cancer. For this reason, WBP Empowerment regarding cervical cancer was carried out to WUS in Medan City Women's Prison. This empowerment aims to increase the knowledge, attitudes and actions of WBP in cervical cancer which is carried out through video media that has been designed with the title Early Introduction to Cervical Cancer with the IVA Test. In this pandemic situation, the community service team provided 2 sinks for washing hands and masks as a form of COVID-19 prevention.